Economic geographies of Asian international financial centers: A sympathetic critique - Huang, Kaixuan; Yeung, Godfrey (ERDKUNDE, 2022)
Through a comprehensive review of economic geography studies on Asian international financial centers (IFCs) published from 2009, this paper aims to provide a sympathetic critique of the key research trajectories of financial geographies and to outline research gaps where economic geographers could contribute to the relevant literature. Economic geographers have identified a prominent change in the geographies of the international finance industry, with the rapid development and the emergence of inter-city networks among Asian IFCs, and suggested how the emerging FinTech industries could reshape the competitive dynamics and thus the financial landscape of IFCs. The literature has unpacked the general mechanisms of how Asian IFCs grow and evolve as well as their spatial patterns but has neglected the macro political-economic contexts that drive the development dynamics of Asian IFCs. To maintain the long-term prospects of financial geography, we call for efforts to theorize (Asian-based) financial geographies and develop the corresponding analytical frameworks with rigorous quantitative and qualitative methods to examine the development trajectories of Asian IFCs and their socio-political and geo-economical mechanisms. Moreover, economic geographers could develop a set of composite parameters to capture the attributes and structures that could (re)shape the development trajectories of inter-city and intra-city financial networks and their level of resilience to external shocks.